2023
DOI: 10.1021/acsami.3c12389
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive Triblock Copolymer for Slow-Release Lubricants under Ocular Conditions

Hongdong Wang,
Qi Wang,
Yunjuan Su
et al.

Abstract: The ocular environment is crucial for a biological lubrication system. An unstable condition of tear film may cause a series of ocular diseases due to serious friction, such as dry eye syndrome, which has drawn extensive attention nowadays. In this study, an in vitro biocompatible superlubricity system, containing thermogelling copolymers (PCGA−PEG−PCGA) and slow-release lubricant (PEG 300/Tween 80), was constructed. First, the sol−gel transition temperature and gel strength of PCGA− PEG−PCGA were adjusted bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Major changes in tear film structure and function are important features of DED . The tear film instability caused by excessive tear evaporation leads to the disturbance of ocular surface homeostasis, which is involved in the pathogenesis of DED. , Certain Asian nations, including China and Japan, have approved diquafosol sodium (DQS) ophthalmic solution as a first-line treatment for DED to improve tear film stability and dry eye symptoms . DQS, a dinucleotide derivative of UTP, is a direct agonist of the purinergic P2Y 2 receptor that stimulates the conjunctiva to secrete water and mucin. , Research has found that the P2Y 2 receptor was closely related to DED .…”
Section: Introductionmentioning
confidence: 99%
“…Major changes in tear film structure and function are important features of DED . The tear film instability caused by excessive tear evaporation leads to the disturbance of ocular surface homeostasis, which is involved in the pathogenesis of DED. , Certain Asian nations, including China and Japan, have approved diquafosol sodium (DQS) ophthalmic solution as a first-line treatment for DED to improve tear film stability and dry eye symptoms . DQS, a dinucleotide derivative of UTP, is a direct agonist of the purinergic P2Y 2 receptor that stimulates the conjunctiva to secrete water and mucin. , Research has found that the P2Y 2 receptor was closely related to DED .…”
Section: Introductionmentioning
confidence: 99%